Nitrogen-doped porous carbon materials: promising catalysts or catalyst supports for heterogeneous hydrogenation and oxidation. Issue 11 (18th April 2016) - Li, Mingming; Xu, Fan; Li, Haoran; Wang, Yong
Abstract : Developing novel and efficient catalysts is a critical step in common heterogeneous hydrogenation and oxidation reactions. Abstract : Developing novel and efficient catalysts is a critical step in common heterogeneous hydrogenation and oxidation reactions. Despite the frequent study of metal oxide-supported catalysts, porous carbon materials have also emerged as valuable potential catalysts. However, due to their highly microporous structures and inferior structural functionalities, traditional activated carbons (ACs) have become increasingly less popular for industrial applications. To deal with the disadvantages of ACs, tremendous efforts have been made to develop novel nitrogen-doped porous carbon (NPC) materials with novel features such as highly porous structures and abundant structural nitrogen heteroatom decoration. As catalysts or catalysts supports, NPC materials have shown superior activities in many applications covering a wide range of heterogeneous hydrogenation and oxidation reactions. In this contribution, we review the fabrication methods for NPC materials used in heterogeneous hydrogenations and oxidations and highlight the intrinsic catalytic mechanisms along with the catalyst design strategies.